An approach to integrate numerical simulation within KBE applications. (2015) - Colombo, Giorgio; Morotti, Roberto; Regazzoni, Daniele; Rizzi, Caterina
This paper presents an approach to automate and integrate numerical simulations within knowledge-based engineering applications to improve the use of simulation tools, especially in small and medium enterprises. Main discussed issues concern: (a) the importance of the CAD model as an input of the process, (b) data migration from CAD to CAE tools, (c) model characterisation, (d) effects of parameters variations, (e) simulation steps, and (f) results evaluation. In addition, formalisation and representation of rules and procedures to automate the design process, in particular the simulation tasks, are presented. Two case studies are described to explain and verify the approach. The first case concerns the design process of centrifugal industrial fans, during which simulation tools are used to verify the correct sizing of impeller blades. The second one is related to a non-industrial process; actually, it regards a medical device, and more precisely lower limb prosthesis. Finally, main results are discussed.